Integration of management systems in food industry companies of Aguascalientes Mexico - Castañeda Fernández, Dulce Inés (2024)
The levels of integration and benefits obtained by 17 companies in the food industry of Aguascalientes that have integrated two or more management systems are reported. Documentary harmonization, partial integration and complete integration were considered as levels and as benefits: workforce benefits, organizational benefits and performance benefits. 92% complied with documentary harmonization, 80% with partial integration and 73,5% with complete integration. The greatest benefits were the performance benefits in improving the quality of products and/or services in 65% of the companies. KEYWORDS: industrial management / total quality management / food industry / environmental management / industrial safety / social responsibility of business.